Can Credit Recipient Household Escape from Poverty? - Tegar Rismanuar Nuryitmawan (Pusbindiklatren Bappenas, 2020)
This study aims to answer whether or notfinancial distribution can play a role in development and poverty alleviation in Indonesia. Households who receive credit are treated as the analysis level and research object. Credit is an instrument to help households escaping from poverty. Some opinions believe that by being given credit, households will be able to boost their economic capacity both in terms of purchasing power or business development capacity. However, to prove this opinion as well as to answer the question, using panel data from the Indonesian Family Live Survey (IFLS) in 2007 and 2014 will attempt to estimate the effect of the probability of households receiving credit on their poverty status. The probability of a credit recipient householdwill be calculated using Propensity Score Matching so that a similarity score of household characteristics will be obtained between those who get credit and those who do not. Using Double Differences, this study will address the description of changes in household poverty status after receiving credit from financial institutions. The PSM calculations results show that there are four variables as credit recipient household’s characteristics, namely collateral ownership, the status of property ownership, history of natural disasters, and gender. Meanwhile, the estimation results on poverty status indicate that credit recipient households have a greater probability of escaping poverty than those who do not receive credit. Therefore, the anti-poverty policy through the transmission of financial institutions is relevant to be prepared. The anti-poverty policy is related to low credit interest rates through government subsidies, public fund placement with low cost of fund, increasing financial literacyand knowledge of the society, and adjusting credit approval based on regional economic conditions.